Haematological quality and age of donor blood issued for paediatric transfusion to four hospitals in sub-Saharan Africa - Uyoga,S; Mpoya,A; Olupot-Olupot,P; Kiguli,S; Opoka,RO; Engoru,C; Mallewa,M; Kennedy,N; M'baya,B; Kyeyune,D; Wabwire,B; Bates,I; et al. (Vox Sanguinis, 2019)
Background and ObjectivesPaediatric blood transfusion for severe anaemia in hospitals in sub-Saharan Africa remains common. Yet, reports describing the haematological quality of donor blood or storage duration in routine practice are very limited. Both factors are likely to affect transfusion outcomes. Materials and MethodsWe undertook 3 audits examiningthe distribution of pack types, haematological quality and storage duration of donor blood used in a paediatric clinical trial of blood at four hospitals in Africa (Uganda and Malawi). ResultsThe overall distribution of whole blood, packed cells(plasma-reduced by centrifugation) and red cell concentrates (RCC) (plasma-reduced by gravity-dependent sedimentation)used in a randomised trial was 40.7% (N=1215), 22.4% (N=669) and 36.8% (N=1099) respectively.The first audit found similar median haematocrits of 57.0% (50.0,74.0), 64.0% (52.0,72.5;p=0.238vs whole blood) and 56.0% (48.0,67.0;p=0.462) in whole blood, RCCand packed cells respectively, which resulted from unclear pack labelling by blood transfusion services (BTS). Retraining of the BTS, hospital blood banks and clinical teams led to, in subsequent audits, significant differences in medianhaematocrit and haemoglobins across the 3 pack types and values within expected ranges. Median storage duration time was 12 days (IQR 6,19) with 18.2% (537/2964) over 21 days in storage. Initially, 9 (2.8%)packswere issued past the recommended duration of storage, dropping to 0.3%(N=7) in the third audit post training. ConclusionThe study highlights the importance of close interactions and education between BTS and clinical services and the importance of haemovigilence to ensure safe transfusion practice.